Presencia de Ehrlichia en canes atendidos en la clínica “Mundo Animal” de la parroquia urbana San Camilo de la ciudad de Quevedo - Medina Posligua, Heidy Yomaira (2024)
Canine Ehrlichiosis is a disease that affects dogs throughout the world. It is caused by bacteria called Ehrlichia spp., transmitted by ticks, and is characterized by a series of clinical signs that can be nonspecific or specific and each one would be linked to a specific stage of ehrlichia, these are: Acute, Subclinical and Clinical. To diagnose the disease, rapid detection tests are performed using specific kits for Ehrlichia Canis. Once the diagnosis is confirmed, treatment focuses on the use of antibiotics such as doxycycline for a prolonged period, usually 4 to 8 weeks. The main objective of this experimental project is to determine the presence of Ehrlichia in dogs treated at the "Mundo Animal" clinic in the city of Quevedo. To achieve this determination, an immunochromatography test was used to qualitatively detect anti-Ehrlichia Canis antibodies in serum, plasma or blood samples from the dogs. A sample of 30 canine patients was selected for this study. In terms of statistical analysis, appropriate methods were used to calculate the total percentage of the presence of Ehrlichia antibodies in the selected sample and to evaluate the association between the presence of the disease and variables such as age, breed and sex of the dogs. The experimental work will provide important information about ehrlichia, its background, development, diagnosis, prevention and treatments.